Osteogenic Effect and Cell Signaling Activation of Extremely Low-Frequency Pulsed Electromagnetic Fields in Adipose-Derived Mesenchymal Stromal Cells - Patrina S. P. Poh; Claudine Seeliger; Marina Unger; Karsten Falldorf; Elizabeth R. Balmayor; Martijn van Griensven (Stem Cells International)
Extremely low-frequency pulsed electromagnetic field (ELF-PEMF) devices have been used in the clinic for the treatment of bone disorders over the past 30 years. However, the underlying mechanism of which ELF-PEMFs exert an effect on tissues at a cellular level is not well understood. Hence, in this study, we explored the potential of different ELF-PEMF signals in modulating human adipose-derived mesenchymal stromal cells’ (hAMSC) osteogenic capability. The cell proliferation rate was assessed using carboxyfluorescein succinimidyl ester (CFSE) method. The osteogenesis potential of cells was determined by alkaline phosphatase (ALP) activity, Alizarin-Red S staining, and RT-qPCR. Finally, the intracellular signaling pathway of a selected ELF-PEMF signal was examined using the PathScan Intracellular Signaling Array. Among the tested ELF-PEMF signals, program 20 (26 Hz) showed activation of the Akt and MAPK/ERK signaling cascade and significant upregulations of collagen I, alkaline phosphatase, and osteocalcin when compared to nonstimulated cells. This study demonstrates the potential of certain ELF-PEMF signal parameters to induce osteogenic differentiation of hAMSC and provides important clues in terms of the molecular mechanisms for the stimulation of osteogenic effects by ELF-PEMF on hAMSC.